2005
DOI: 10.1002/art.20874
|View full text |Cite
|
Sign up to set email alerts
|

Joint inflammation and chondrocyte death become independent of Fcγ receptor type III by local overexpression of interferon‐γ during immune complex–mediated arthritis

Abstract: Objective. It has previously been shown that the onset and the degree of joint inflammation during immune complex (IC)-mediated arthritis depend on Fc␥ receptor type III (Fc␥RIII). Local adenoviral overexpression of interferon-␥ (IFN␥) in the knee joint prior to onset of IC-mediated arthritis aggravated severe cartilage destruction. In Fc␥RI Ϫ/Ϫ mice, however, chondrocyte death was not enhanced by IFN␥, whereas matrix metalloproteinase (MMP)-mediated aggrecan breakdown was markedly elevated, suggesting a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In the early phase of CIA, cartilage destruction correlated with the level of inflammation, which was predominantly dependent on Fc␥RIII (Fig. 2), confirming results from studies in other arthritis models (13,18). The prominent role of the low affinity Fc␥RIII can be explained by its 1) broad expression pattern (macrophages, neutrophils, mast cells, NK cells, and NKT cells); 2) relatively high basal expression level; and 3) broad specificity for IgG (IgG1 Ͼ IgG2a Ͼ IgG2b).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the early phase of CIA, cartilage destruction correlated with the level of inflammation, which was predominantly dependent on Fc␥RIII (Fig. 2), confirming results from studies in other arthritis models (13,18). The prominent role of the low affinity Fc␥RIII can be explained by its 1) broad expression pattern (macrophages, neutrophils, mast cells, NK cells, and NKT cells); 2) relatively high basal expression level; and 3) broad specificity for IgG (IgG1 Ͼ IgG2a Ͼ IgG2b).…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown that activation of infiltrating or resident cells in the joint leads to severe cartilage destruction, such as matrix metalloproteinase-induced damage or chondrocyte death (17). Activating Fc␥R have been implicated in this process in the Ag-induced arthritis (AIA) model (13,18).…”
mentioning
confidence: 99%
“…In FcγRIII KO mice IFNγ-most likely through increasing FcγRI expression on resident macrophages in the joint-is able to bypass FcγRIII requirement for inflammation during ICA. This study also proves that both FcγRI and FcγRIII can contribute to MMP-mediated destruction of cartilage [70].…”
Section: Immune Complex-mediated Arthritismentioning
confidence: 53%
“…FcγRI expression during AIA is upregulated by T cell derived IFNγ, hence, late cartilage destruction becomes entirely FcγRI-dependent. Artificially induced local overexpression of IFNγ by adenovirus expression vectors in the knee during ICA results in elevated chondrocyte death in wild-type and FcγRIII KO mice, but not in FcγRI KO mice [69,70]. However, MMP-induced proteoglycan damage is elevated in FcγRI KO mice as well, indicating that FcγRIII-when upregulated by IFNγ-is able to mediate this process [69].…”
Section: Immune Complex-mediated Arthritismentioning
confidence: 88%
“…2) or Con A (data not shown), suggesting that the elevated T cell IFN-g release in mice lacking CD1d-dependent NKTs was not due to a general higher activation status of T cells in these mice. Even though IFN-g has recently been implicated as a regulatory cytokine in arthritis (52), others have shown that IFN-g worsens CIA and is important for cartilage destruction during immune complex-mediated arthritis (53,54).…”
Section: B6mentioning
confidence: 99%